Minimalistic SDHC-SPI hardware reader module for boot loader applications. (September 2017) - Ruiz-de-Clavijo, Paulino; Ostúa, Enrique; Bellido, Manuel-J.; Juan, Jorge; Viejo, Julián; Guerrero, David
Abstract: This paper introduces a low-footprint full hardware boot loading solution for FPGA-based Programmable Systems on Chip. The proposed module allows loading the system code and data from a standard SD card without having to re-program the whole embedded system. The hardware boot loader is processor independent and removes the need of a software boot loader and the related memory resources. The hardware overhead introduced is manageable, even in low-range FPGA chips, and negligible in mid- and high-range devices. The implementation of the SD card reader module is explained in detail and an example of a multi-boot loader is offered as well. The multi-boot loader is implemented and tested with the Xilinx's Picoblaze microcontroller.